Indonesian archaeological photographs : photo collection of the National Research Centre of Archaeology of the Republic of Indonesia 1901-1956 at the Kern Institute, University of Leiden (Asian law. South East Asia ;, 1983)
Contains photographs of Indonesian antiquities.